Perceived Social Support as Moderator Variable Between the Attitude of Becoming A Social Entrepreneur (ATB) On Social Entrepreneurial Intention - Purbo Jadmiko (Journal of Islamic Economic and Business Research, 2021)
This research is motivated by the development of the social entrepreneurship topic among students. This research focused on analyzing the antecedents of social entrepreneurial intention by involving attitudes towards becoming a social entrepreneur (ATB) and social support. A total of 208 students at Universitas Bung Hatta became respondents with the criteria of having taken lectures for at least two semesters. Moderated Regression Analysis (MRA) method was used to test the moderating hypothesis (perceived social support). This research shows that the higher the perceived social support perceived by students, the stronger the influence between ATB on social entrepreneurial intention. In this research, perceived social support plays a moderator role (purely moderated) in the relationship between ATB and social entrepreneurial intention. In addition, interesting findings of the moderating effect by gender where women have a higher moderating effect than men. One of the limitations of this research is that the sample was only within the scope of students. Hopefully, future researches can expand the scope of the sample, such as involving social entrepreneurs, so that the generalization of research results can be better. In addition, this research still has not linked several elements of context and factors, including culture, gender differences, personality characteristics, to the context of differences in developed and developing countries (local wisdom).